PQRI Workshop: Model-Informed Drug Development (MIDD) Approaches in Pediatric Formulation Development - Gilbert J. Burckart; Susan Abdel-Rahman; Caleb Choi; M. Petrea Cober; James E. Cummins; Nikoletta Fotaki; Daniel Gonzalez; David Harris; Neil Parrott; Hardikkumar Patel; Fang Wu; Andreas Abend (The AAPS Journal, 2026)
In February of 2024, the Product Quality Research Institute held a virtual workshop entitled “Model-Informed Drug Development (MIDD) Approaches in Pediatric Formulation Development.” The workshop covered a range of topics related to pediatric formulation development and testing, including dissolution testing and applications to modeling drug absorption in developing pediatric patients. Workshop speakers reviewed the progress that has been made to advance our understanding of ontogeny related processes that drive interactions with product formulations and inform pediatric product development. They discussed recently constructed pediatric biorelevant models that provide more realistic information about drug dissolution in pediatric patients and their use in physiologically based models to produce data for regulatory submissions. Despite the progress, opportunities remain to expand the fund of knowledge on pediatric absorptive processes that will support the development of pediatric-friendly drug formulations. Graphical Abstract

Optimization of In Vitro CYP3A4 TDI Assay Conditions and Use of Derived Parameters for Clinical DDI Risk Assessment Using Static and Dynamic Models - Alessandra Pugliano; Aynur Ekiciler; Lena Preiss; Neil John Parrott; Pieter Annaert; Kenichi Umehara (The AAPS Journal, 2025)
Cytochrome P450 3A4 (CYP3A4) is a key target for time-dependent inhibition (TDI) assessment during drug development. However, translating in vitro TDI data to in vivo drug-drug interaction (DDI) risk remains challenging due to the acknowledged overestimation when incorporating in vitro kinetics in predictive models. We investigated different in vitro TDI assay conditions in human liver microsomes (HLM) and evaluated their impact on the predictive accuracy for CYP3A4-related DDI for 32 marketed drugs. Considering assay sensitivity and in vivo DDI prediction accuracy with mechanistic static modeling (MSM), optimal incubation parameters were identified as: a pre-incubation time of 40 min for precipitants and 10 min incubation time for CYP3A4 substrate midazolam (10 μM) at 0.1 mg/mL HLM. A tendency to overestimate the DDI magnitude (AFE = 4.83, AAFE = 4.87) was still observed in MSM when using the unbound drug inhibition constant (KI, u ) and maximum inactivation rate (k inact ), measured under optimized incubation conditions. Improved predictions were achieved when applying the same parameters in physiologically-based pharmacokinetic (PBPK) models (AFE = 1.94, AAFE = 2.13), with 60% of predicted AUCR falling in the twofold range. These findings highlighted the importance of optimizing in vitro TDI incubation conditions, together with evaluating the benefits and limitations of numerical prediction approaches for predicting clinically significant CYP3A4 TDI effects with mechanistic static and PBPK models. Graphical Abstract

Mechanistic Modeling of In Vitro Biopharmaceutic Data for a Weak Acid Drug: A Pathway Towards Deriving Fundamental Parameters for Physiologically Based Biopharmaceutic Modeling - Venkata Krishna Kowthavarapu; Nitin Bharat Charbe; Churni Gupta; Tatiana Iakovleva; Cordula Stillhart; Neil John Parrott; Stephan Schmidt; Rodrigo Cristofoletti (The AAPS Journal, 2024)

Streamlining Food Effect Assessment — Are Repeated Food Effect Studies Needed? An IQ Analysis - Filippos Kesisoglou; Sumit Basu; Tejashree Belubbi; Philip Bransford; John Chung; Stephanie Dodd; Michael Dolton; Tycho Heimbach; Priyanka Kulkarni; Wen Lin; Andrea Moir; Neil Parrott; et al. (The AAPS Journal, 2023)

Current Approaches for Predicting Human PK for Small Molecule Development Candidates: Findings from the IQ Human PK Prediction Working Group Survey - Carl Petersson; Xin Zhou; Joerg Berghausen; David Cebrian; Michael Davies; Kevin DeMent; Peter Eddershaw; Arian Emami Riedmaier; Alix F. Leblanc; Nenad Manveski; Punit Marathe; Panteleimon D. Mavroudis; et al. (The AAPS Journal, 2022)

Use of Physiologically Based Pharmacokinetic Modeling for Predicting Drug–Food Interactions: Recommendations for Improving Predictive Performance of Low Confidence Food Effect Models - Christian Wagner; Filippos Kesisoglou; Xavier J. H. Pepin; Neil Parrott; Arian Emami Riedmaier (The AAPS Journal, 2021)

Understanding Mechanisms of Food Effect and Developing Reliable PBPK Models Using a Middle-out Approach - Xavier J. H. Pepin; James E. Huckle; Ravindra V. Alluri; Sumit Basu; Stephanie Dodd; Neil Parrott; Arian Emami Riedmaier (The AAPS Journal, 2021)

Correction to: Use of Physiologically Based Pharmacokinetic (PBPK) Modeling for Predicting Drug-Food Interactions: an Industry Perspective - Arian Emami Riedmaier; Kevin DeMent; James Huckle; Phil Bransford; Cordula Stillhart; Richard Lloyd; Ravindra Alluri; Sumit Basu; Yuan Chen; Varsha Dhamankar; Stephanie Dodd; Priyanka Kulkarni; et al. (The AAPS Journal, 2021)

Correction to: In Vitro to In Vivo Extrapolation of Metabolic Clearance for UGT Substrates Using Short-Term Suspension and Long-Term Co-cultured Human Hepatocytes - Luca Docci; Florian Klammers; Aynur Ekiciler; Birgit Molitor; Kenichi Umehara; Isabelle Walter; Stephan Krähenbühl; Neil Parrott; Stephen Fowler (The AAPS Journal, 2020)

In Vitro to In Vivo Extrapolation of Metabolic Clearance for UGT Substrates Using Short-Term Suspension and Long-Term Co-cultured Human Hepatocytes - Luca Docci; Florian Klammers; Aynur Ekiciler; Birgit Molitor; Kenichi Umehara; Isabelle Walter; Stephan Krähenbühl; Neil Parrott; Stephen Fowler (The AAPS Journal, 2020)

Construction and Verification of Physiologically Based Pharmacokinetic Models for Four Drugs Majorly Cleared by Glucuronidation: Lorazepam, Oxazepam, Naloxone, and Zidovudine - Luca Docci; Kenichi Umehara; Stephan Krähenbühl; Stephen Fowler; Neil Parrott (The AAPS Journal, 2020)

Use of Physiologically Based Pharmacokinetic (PBPK) Modeling for Predicting Drug-Food Interactions: an Industry Perspective - Arian Emami Riedmaier; Kevin DeMent; James Huckle; Phil Bransford; Cordula Stillhart; Richard Lloyd; Ravindra Alluri; Sumit Basu; Yuan Chen; Varsha Dhamankar; Stephanie Dodd; Priyanka Kulkarni; et al. (The AAPS Journal, 2020)
The effect of food on pharmacokinetic properties of drugs is a commonly observed occurrence affecting about 40% of orally administered drugs. Within the pharmaceutical industry, significant resources are invested to predict and characterize a clinically relevant food effect. Here, the predictive performance of physiologically based pharmacokinetic (PBPK) food effect models was assessed via de novo mechanistic absorption models for 30 compounds using controlled, pre-defined in vitro , and modeling methodology. Compounds for which absorption was known to be limited by intestinal transporters were excluded in this analysis. A decision tree for model verification and optimization was followed, leading to high, moderate, or low food effect prediction confidence. High (within 0.8- to 1.25-fold) to moderate confidence (within 0.5- to 2-fold) was achieved for most of the compounds (15 and 8, respectively). While for 7 compounds, prediction confidence was found to be low (> 2-fold). There was no clear difference in prediction success for positive or negative food effects and no clear relationship to the BCS category of tested drug molecules. However, an association could be demonstrated when the food effect was mainly related to changes in the gastrointestinal luminal fluids or physiology, including fluid volume, motility, pH, micellar entrapment, and bile salts. Considering these findings, it is recommended that appropriately verified mechanistic PBPK modeling can be leveraged with high to moderate confidence as a key approach to predicting potential food effect, especially related to mechanisms highlighted here.

Physiologically Based Absorption Modelling to Explore the Impact of Food and Gastric pH Changes on the Pharmacokinetics of Entrectinib - Neil Parrott; Cordula Stillhart; Marc Lindenberg; Bjoern Wagner; Karey Kowalski; Elena Guerini; Nassim Djebli; Georgina Meneses-Lorente (The AAPS Journal, 2020)

Global Sensitivity Analysis of the Rodgers and Rowland Model for Prediction of Tissue: Plasma Partitioning Coefficients: Assessment of the Key Physiological and Physicochemical Factors That Determine Small-Molecule Tissue Distribution - Estelle Yau; Andrés Olivares-Morales; Michael Gertz; Neil Parrott; Adam S. Darwich; Leon Aarons; Kayode Ogungbenro (The AAPS Journal, 2020)

Impact of Intracellular Concentrations on Metabolic Drug-Drug Interaction Studies - Andrea Treyer; Mohammed Ullah; Neil Parrott; Birgit Molitor; Stephen Fowler; Per Artursson (The AAPS Journal, 2019)

Simulating the Impact of Elevated Levels of Interleukin-6 on the Pharmacokinetics of Various CYP450 Substrates in Patients with Neuromyelitis Optica or Neuromyelitis Optica Spectrum Disorders in Different Ethnic Populations - Krishna K. Machavaram; Chihiro Endo-Tsukude; Kimio Terao; Katherine L. Gill; Oliver J. Hatley; Iain Gardner; Neil Parrott; Patricia Sanwald Ducray (The AAPS Journal, 2019)

PBPK Absorption Modeling: Establishing the In Vitro–In Vivo Link—Industry Perspective - Cordula Stillhart; Xavier Pepin; Christophe Tistaert; David Good; An Van Den Bergh; Neil Parrott; Filippos Kesisoglou (The AAPS Journal, 2019)

In Vivo Predictive Dissolution and Simulation Workshop Report: Facilitating the Development of Oral Drug Formulation and the Prediction of Oral Bioperformance - Yasuhiro Tsume; Sanjaykumar Patel; Nikoletta Fotaki; Christel Bergstrӧm; Gordon L. Amidon; James G. Brasseur; Deanna M. Mudie; Duxin Sun; Marival Bermejo; Ping Gao; Wei Zhu; David C. Sperry; et al. (The AAPS Journal, 2018)

Investigating Oral Absorption of Carbamazepine in Pediatric Populations - Philip Kohlmann; Cordula Stillhart; Martin Kuentz; Neil Parrott (The AAPS Journal, 2017)

Characterising Drug Release from Immediate-Release Formulations of a Poorly Soluble Compound, Basmisanil, Through Absorption Modelling and Dissolution Testing - Cordula Stillhart; Neil J. Parrott; Marc Lindenberg; Pascal Chalus; Darren Bentley; Anikó Szepes (The AAPS Journal, 2017)

Metabolic Profiling of Human Long-Term Liver Models and Hepatic Clearance Predictions from In Vitro Data Using Nonlinear Mixed-Effects Modeling - Nicole A. Kratochwil; Christophe Meille; Stephen Fowler; Florian Klammers; Aynur Ekiciler; Birgit Molitor; Sandrine Simon; Isabelle Walter; Claudia McGinnis; Johanna Walther; Brian Leonard; Miriam Triyatni; et al. (The AAPS Journal, 2017)

Progress in Prediction and Interpretation of Clinically Relevant Metabolic Drug-Drug Interactions: a Minireview Illustrating Recent Developments and Current Opportunities - Stephen Fowler; Peter N. Morcos; Yumi Cleary; Meret Martin-Facklam; Neil Parrott; Michael Gertz; Li Yu (Current Pharmacology Reports, 2017)

Metabolic impact of 100% fruit juice consumption on antioxidant/oxidant status and lipid profiles of adults: An Evidence-Based review - Kristi Crowe-White; J. Scott Parrott; Kim S. Stote; Melissa Gutschall; Sue Benson-Davies; Elizabeth Droke; Carol E. O'Neil; Taylor Wolfram; Paula Ziegler (Critical Reviews in Food Science and Nutrition, 2017)

Physiologically Based Absorption Modeling to Explore the Impact of Food and Gastric pH Changes on the Pharmacokinetics of Alectinib - Neil J Parrott; Li J Yu; Ryusuke Takano; Mikiko Nakamura; Peter N. Morcos (The AAPS Journal, 2016)

Erratum to: Characterization of Pharmacokinetics in the Göttingen Minipig with Reference Human Drugs: An In Vitro and In Vivo Approach - Floriane Lignet; Eva Sherbetjian; Nicole Kratochwil; Russell Jones; Claudia Suenderhauf; Michael B. Otteneder; Thomas Singer; Neil Parrott (Pharmaceutical Research, 2016)

Characterization of Pharmacokinetics in the Göttingen Minipig with Reference Human Drugs: An In Vitro and In Vivo Approach - Floriane Lignet; Eva Sherbetjian; Nicole Kratochwil; Russell Jones; Claudia Suenderhauf; Michael B. Otteneder; Thomas Singer; Neil Parrott (Pharmaceutical Research, 2016)

Using Physiologically Based Pharmacokinetic (PBPK) Modelling to Gain Insights into the Effect of Physiological Factors on Oral Absorption in Paediatric Populations - Angela Villiger; Cordula Stillhart; Neil Parrott; Martin Kuentz (The AAPS Journal, 2016)

Simulation-Based Evaluation of PK/PD Indices for Meropenem Across Patient Groups and Experimental Designs - Anders N. Kristoffersson; Pascale David-Pierson; Neil J. Parrott; Olaf Kuhlmann; Thierry Lave; Lena E. Friberg; Elisabet I. Nielsen (Pharmaceutical Research, 2016)

Impact of 100% Fruit Juice Consumption on Diet and Weight Status of Children: An Evidence-based Review - Kristi Crowe-White; Carol E. O'Neil; J. Scott Parrott; Sue Benson-Davies; Elizabeth Droke; Melissa Gutschall; Kim s. Stote; Taylor Wolfram; Paula Ziegler (Critical Reviews in Food Science and Nutrition, 2016)

Evaluating a physiologically based pharmacokinetic model for prediction of omeprazole clearance and assessing ethnic sensitivity in CYP2C19 metabolic pathway - Sheng Feng; Yumi Cleary; Neil Parrott; Pei Hu; Cornelia Weber; Yongqing Wang; Ophelia Q. P. Yin; Jun Shi (European Journal of Clinical Pharmacology, 2015)

Quantitative ADME Proteomics – CYP and UGT Enzymes in the Beagle Dog Liver and Intestine - Aki T. Heikkinen; Arno Friedlein; Mariette Matondo; Oliver J. D. Hatley; Aleksanteri Petsalo; Risto Juvonen; Aleksandra Galetin; Amin Rostami-Hodjegan; Ruedi Aebersold; Jens Lamerz; Tom Dunkley; Paul Cutler; et al. (Pharmaceutical Research, 2015)

Pharmacokinetics of Paracetamol in Göttingen Minipigs: In Vivo Studies and Modeling to Elucidate Physiological Determinants of Absorption - Claudia Suenderhauf; Gerald Tuffin; Helle Lorentsen; Hans-Peter Grimm; Christophe Flament; Neil Parrott (Pharmaceutical Research, 2014)

Physiologically Based Absorption Modelling to Predict the Impact of Drug Properties on Pharmacokinetics of Bitopertin - Neil Parrott; Dominik Hainzl; Emmanuel Scheubel; Siegfried Krimmer; Christophe Boetsch; Elena Guerini; Meret Martin-Facklam (The AAPS Journal, 2014)

In Vitro and Ex Vivo Investigation of the Impact of Luminal Lipid Phases on Passive Permeability of Lipophilic Small Molecules Using PAMPA - Constantinos Markopoulos; Georgios Imanidis; Maria Vertzoni; Mira Symillides; Neil Parrott; Christos Reppas (Pharmaceutical Research, 2013)

A Physiologically Based Pharmacokinetic Model of the Minipig: Data Compilation and Model Implementation - Claudia Suenderhauf; Neil Parrott (Pharmaceutical Research, 2013)

Mass Spectrometry-Based Quantification of CYP Enzymes to Establish In Vitro/In Vivo Scaling Factors for Intestinal and Hepatic Metabolism in Beagle Dog - Aki T. Heikkinen; Arno Friedlein; Jens Lamerz; Peter Jakob; Paul Cutler; Stephen Fowler; Tara Williamson; Roberto Tolando; Thierry Lave; Neil Parrott (Pharmaceutical Research, 2012)